2012
DOI: 10.5897/ajb12.1319
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a newly isolated green microalga Scenedesmus sp. as a potential source of biodiesel

Abstract: An oil-producing microalga SP-01 belonging to the genus Scenedesmus was shown to be able to grow on a media containing 5 to 30 g L -1 NaCl. Under mixotrophic condition, the maximum cell dry weight of 3.1 g L -1 and specific growth rate of 0.034 h -1 were obtained at 0.5 g L -1 NaNO 3 and 6 g L -1 acetate. The effects of salinity on the biomass, lipid, and carotenoid productions of the alga SP-01 in mixotrophic mode were investigated. The biomass productivity increased with increasing NaNO 3 concentrations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
1
3
1
Order By: Relevance
“…In addition, in comparison to the combined effects of N limitation (130 mg L −1 NaNO 3 ), high salinity (343 mM NaCl), and high light intensity (200 µmol m −2 s −1 ) on Scenedesmus sp. in a similar study, lipid productivity and lipid content of S. rubescens KNUA042 cells in the present study were higher [47]. Similarly, in H. pluvialis, combinations of three stress factors (high light intensity + salinity, high light intensity + iron, or salinity + iron) also produced a sustained increase in by-products.…”
Section: Lipid and Biomass Productivity Under Abiotic Stress In The P...supporting
confidence: 86%
See 2 more Smart Citations
“…In addition, in comparison to the combined effects of N limitation (130 mg L −1 NaNO 3 ), high salinity (343 mM NaCl), and high light intensity (200 µmol m −2 s −1 ) on Scenedesmus sp. in a similar study, lipid productivity and lipid content of S. rubescens KNUA042 cells in the present study were higher [47]. Similarly, in H. pluvialis, combinations of three stress factors (high light intensity + salinity, high light intensity + iron, or salinity + iron) also produced a sustained increase in by-products.…”
Section: Lipid and Biomass Productivity Under Abiotic Stress In The P...supporting
confidence: 86%
“…These results are similar to the maximum yield of 41% obtained for Scenedesmus sp. SP-1 grown in culture media supplemented with 130 mg L −1 NaNO 3 [47]. The lipid content in the S. rubescens KNUA042 cells in our study was higher than the moderate lipid content of 10%-39% obtained from other Scenedesmus species [48].…”
Section: Lipid and Biomass Productivity Under Abiotic Stress In The P...contrasting
confidence: 61%
See 1 more Smart Citation
“…Other research has corroborated that Scenedesmus sp. can grow optimally at salinities between 0 and 10,000 mg L −1 , with growth possible but inhibited between 10,000 and 30,000 mg L −1 [52]. These research findings indicate that some freshwater algae such as the C. reinhardtii, S. rotundus, and Scenedesmus sp.…”
Section: Selection Of Algal Species Based On the Salinity Of Pwmentioning
confidence: 65%
“…Furthermore, the species level classification of algal sequences under the classification Plantae from the slime sample, indicated that 70% of plastid sequences belonged to the species S. rotundus. This alga is known to be found in a wide range of sub-tropical and desert locations, which indicates the climate (i.e., elongated periods of desiccation and tropical rainfall) experienced by this microalgal species at the PW treatment plant [52][53][54][55][56]. The salinity of the PW treatment plant at the time of sampling was between 5021 and 7294 mg L −1 , which typically is in the range of moderately saline water.…”
Section: Selection Of Algal Species Based On the Salinity Of Pwmentioning
confidence: 99%